Policing Delhi urbanization, crime, and law enforcement - Mishra, O. P. (Om Prakash), 1963- (New Delhi ; Oxford : Oxford University Press, 2011)
Set against the backdrop of the capital's history, culture, and socio-political scenario, this is a full-length study of the connection between rapid urbanization, rising crime, and law enforcement in Delhi.
Revison of author's thesis (Ph. D.--Jawaharlal Nehru University, 2009).
Description based on print version record.
Includes bibliographical references.
Keywords: Police -- India -- New Delhi; Crime -- India -- New Delhi